Programa de fertilización de seis variedades de café (Coffea sp), etapa de producción. - Castillo Ronquillo, Ronald Augusto (2022)
The fertilization program of six varieties of coffee (Coffea sp) was evaluated in the production stage, the contribution of macro and micro nutrients of the soil was determined, the agronomic response of the coffee crop with the fertilization program was analyzed and the production costs of the coffee crop in the production stage were established. The research project was carried out at the "Sacha wiwa" Experimental Center. Four treatments were used with four fertilization programs and a control, which are based on organic and inorganic fertilization. The results show that the contribution of macro and micro nutrients of the soil at the beginning of the experiment, the pH medium acid. The organic matter was medium and low. Macro nutrients are low and micronutrients are fluctuating between low, medium and high. At the end of the experiment the three experimental plots have acid pH, organic matter with high levels. The macro nutrients were mostly low. The agronomic response of the coffee crop with the fertilization program in the production stage resulted in the highest averages in plant height, variety NP2024 with the 100% conventional treatment; in stem diameter and leaf circumference the NP2024 variety with the 1500 kg ha treatment. The production costs of the coffee crop in the production stage were estimated and the costs for 100% conventional fertilization were the highest with 41.61 dollars, while the costs for the fertilizer formulas were 41.00 USD (100 kg ha); 38.82 USD (1500 kg ha) and 38.62 USD (2000 kg ha).